2020 IEEE/RSJ International Conference on Intelligent Robots and Systems (IROS) 2020
DOI: 10.1109/iros45743.2020.9341337
|View full text |Cite
|
Sign up to set email alerts
|

Affordance-Based Mobile Robot Navigation Among Movable Obstacles

Abstract: Avoiding obstacles in the perceived world has been the classical approach to autonomous mobile robot navigation. However, this usually leads to unnatural and inefficient motions that significantly differ from the way humans move in tight and dynamic spaces, as we do not refrain interacting with the environment around us when necessary. Inspired by this observation, we propose a framework for autonomous robot navigation among movable obstacles (NAMO) that is based on the theory of affordances and contact-implic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…It was shown that it is possible to reduce the evacuation time by creating new pathways for the humans that are leaving a dangerous environment. In [24] the role of computer vision is explored in order to facilitate the solution of NAMO problems. In particular, the problem of how affordances detection can be used to create open loop NAMO plans.…”
Section: Related Workmentioning
confidence: 99%
“…It was shown that it is possible to reduce the evacuation time by creating new pathways for the humans that are leaving a dangerous environment. In [24] the role of computer vision is explored in order to facilitate the solution of NAMO problems. In particular, the problem of how affordances detection can be used to create open loop NAMO plans.…”
Section: Related Workmentioning
confidence: 99%
“…The methods have been used on humanoid robots and wheeled ones, up to an extend (either with known environments or via open-loop controllers), as well as for robot arm manipulation [37]. Recently they have been extended for socially-aware navigation [38], [39], navigation using scene affordances [40], or even sim2real navigation [41]. In our paper, we are utilizing an object pushing action, based on the NAMO algorithm, introduced in [35], [38], using the legs of the hybrid robot.…”
Section: A Related Workmentioning
confidence: 99%
“…One of the conventional approaches is the task and motion planning (TAMP) method which combines task planning in symbolic space and motion planning in the configuration space [8]- [10]. The other approach is navigation among movable obstacles (NAMO), which is a navigation method that considers not only avoiding obstacles but also interaction with movable obstacles [11], [12]. The feasibility of actions in real space is verified using these methods based on the following two procedures.…”
Section: Related Work a Task Planning And Motion Planningmentioning
confidence: 99%
“…The conditions of the graph representation methods are shown in Table 8. The comparison method 2.1 represents the action possibility in the current environment as well as the methods to understand the objects to be removed in real space [8], [12]. In this method, the movable object positions were traversable, and the cost of removing the object was added when the robot passes through the position.…”
Section: Experiments 2: Verification Of Action Graph Structure 1) Experimental Conditionsmentioning
confidence: 99%